Institutional communication and crisis management mechanisms in the Algerian local administration - فريدة بوبكري (International Journal of Social Communication, 2023)
This study aims to highlight the importance and role of institutional communication in crisis management at the level of the Algerian local administration, as there are many places and different times, and the crises are classified in their types and areas of influence, and what they leave behind in terms of destruction, setback, damage and even economic backwardness, and the surprise of sectoral and dilapidated budgets in their origin, to record The forced return to the starting point, if its location is known. Policies were drawn up and programs implemented, and rose to be in the field of institutional communication. Laws were explained and followed by instructions to manage human resources and control the availability of means, monitor their developments and be able to know the summary of their results, so that the field of dealing with new crises is renewed according to data that has come. They are similar only on paper, and in their definitions only. Therefore, in order to establish the success of managing the crisis, there must be an aspect of institutional communication and operational coordination between all actors in their sectors, trainings, and preparations.